Study of Cursive Calligraphy of wu zhen(吳鎮)’s Ink bambooo Collection - 쥬로엔 덩; 이재우 (International Journal of Advanced Culture Technology(IJACT), 2022)
The purpose of this paper is to summarize the cursive script of traditional calligraphy and develop further possibilities based on the study of the painting and postscript of Ink bambooo, which was painted by wu zhen （吳鎮）during the Yuan Dynasty. The second section in this paper provides a summary of wu zhen（吳鎮）’s life, in addition to "Ink bambooo" and its painting postscript. The third and fourth sections are focused on analyzing the cursive script in the painting postscript of Ink bambooo, including the left-and-right structure, head prefix symbols, and bottom prefix symbols. The aim of this paper is the study of cursive script, and the theories and methods of the characters proposed by Dr. Cai Yonggui (from Fujian Normal University) and Dr. Liu Dongqin (from Southeast University) will be used to provide a summary. The presentation of the research results of this paper is designed to develop further possibilities for this type of traditional calligraphy.